Call your Mothers! Sámi Culture-Based Curriculum Development Based on Mathematics Teachers, Students and Mothers in Joint Research Actions - Nutti, Ylva Jannok; Fyhn, Anne Birgitte; Eira, Ellen J. Sara; Sandvik, Svein Ole; Børresen, Tore; Hætta, Ole Einar; Somby, Josefine; Gaup, Kristine Marie (International Journal about Parents in Education, 2023)
This paper describes the collaboration between home and school during the planning of a mathematics teaching experiment involving ruvden, a Sámi braiding procedure. The experiment was conducted in a Sámi lower secondary school. In Sámi schools, Sámi language and culture shall constitute the basis for the teaching, but no cultural implementation usually takes place in the mathematics teaching. The teachers’ investigations of ruvden took place in collaboration with researchers and students during workshops, meetings and math days. The participants investigated the braiding procedure with different numbers of yarns; during one workshop, two girls’ mothers were invited to participate. The contributions of these new participants opened up for research questions with a focus on home-and-school cooperation. The first research question is: How did the mothers experience their involvement in the development of the Sámi culture-based teaching experiment? Analyses of that question prepared for another research question: How may home-and-school collaboration contribute to culture-based curriculum development? The mothers experienced their involvement positive, and the home-and-school cooperation had even implications for the content of the teaching experiment. The home-and-school collaboration took part on the basis of the perspective of shared responsibilities.